1999
DOI: 10.1042/0264-6021:3410147
|View full text |Cite
|
Sign up to set email alerts
|

The DmpA aminopeptidase from Ochrobactrum anthropi LMG7991 is the prototype of a new terminal nucleophile hydrolase family

Abstract: The DmpA (d-aminopeptidase A) protein produced by Ochrobactrum anthropi hydrolyses p-nitroanilide derivatives of glycine and d-alanine more efficiently than that of l-alanine. When regular peptides are utilized as substrates, the enzyme behaves as an aminopeptidase with a preference for N-terminal residues in an l configuration, thus exemplifying an interesting case of stereospecificity reversal. The best-hydrolysed substrate is l-Ala-Gly-Gly, but tetra- and penta-peptides are also efficiently hydrolysed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 37 publications
2
42
0
Order By: Relevance
“…The results of our inhibition studies revealed that BapA was inhibited neither by the protease inhibitors phenylmethylsulfonyl fluoride and EDTA nor by divalent metal ions and reducing agents. No inhibitor has been found so far for DmpA from O. anthropi (9). BapA remains active even in the presence of 50% (vol/vol) ethylene glycol during purification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of our inhibition studies revealed that BapA was inhibited neither by the protease inhibitors phenylmethylsulfonyl fluoride and EDTA nor by divalent metal ions and reducing agents. No inhibitor has been found so far for DmpA from O. anthropi (9). BapA remains active even in the presence of 50% (vol/vol) ethylene glycol during purification.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we named the enzyme BapA for ␤-peptidyl aminopeptidase. DmpA from O. anthropi is described as the prototype of a new family of Ntn hydrolases (23), which are activated by a self-catalyzed protein splicing process between two conserved residues to open access to the catalytic N-terminal residue (serine, threonine, or cysteine) (9). The two subunits of DmpA from O. anthropi have molecular masses of 26.6 and 13.7 kDa, respectively; this corresponds well with the molecular masses of the BapA subunits.…”
Section: Discussionmentioning
confidence: 99%
“…The 10 N-terminal residues obtained by protein sequencing were identical to those deduced from the nucleotide sequence starting from Thr267, demonstrating that NylC A and NylC K were subjected to specific cleavage at Asn266/Thr267, which has previously been identified as a cleavage site in NylC p2 (4). The observed processing is a specific feature of the N-terminal nucleophile (Ntn) hydrolase family, in which cleavage is performed auto-catalytically to generate two subunits (1,2,3,8).…”
Section: Fig 2 Tlc Of Various Nylon Oligomers and Reaction Productsmentioning
confidence: 99%
“…DmpA is an aminopeptidase that hydrolyzes peptides, with a preference for N-terminal residues in an L-configuration (L-Ala-Gly-Gly) and also amide or ester derivatives of D-Ala (19). BapA hydrolyzes ␤-oligopeptides and mixed ␤/␣-oligopeptides with a ␤-amino acid residue at the N terminus (20).…”
Section: Subunit Structure and Function Relationship With Other N-tn mentioning
confidence: 99%